Repeated photoswitching performance of azobenzenes adsorbed on gold surfaces: a balance between space, intermolecular interactions, and phase separation. (30th January 2017) - Kaneta, Mitsuyuki; Honda, Takumu; Onda, Ken; Han, Mina
Abstract : A delicate balance between space, intermolecular interactions, and phase separation plays an important role in forming repeatedly photoswitchable monolayers. Abstract : Single-component azobenzene thiol (Me-SH) and two-component azobenzene dodecyl disulfide (Me-SS) have been used to understand how "space" necessary for trans ↔ cis photoisomerization, "intermolecular interactions" and "phase separation" affects the repeated photoswitching ability of azobenzene units on flat gold surfaces. Me-SH self-assembled monolayers (SAMs) with available space and π–π stacking interactions between photoswitchable azobenzene units showed ∼51% of the first trans -to- cis photoisomerization and good photoswitching performance in response to alternating irradiation with UV and visible light. On the other hand, our absorption spectral data and AFM observations suggest that each chemical component of Me-SS did not move continuously on a flat gold surface and was almost fixed after partially phase-separated SAM formation. The first trans -to- cis photoconversion of the Me-SS SAMs with additional free space arising from phase separation reached as high as 75 ± 3%. Repeated irradiation of the Me-SS SAMs with UV and visible light seems to cause (i) out-of-plane (homeotropic and/or oblique) reorientation and/or (ii) random arrangements of mixed trans - and cis -azobenzenes. Consequently, the initial excellent photoswitching ability declined gradually as the number of repeated irradiations increased. The observations indicate that a balance between space, intermolecular interactions, and phase separation plays an important role in forming repeatedly photoswitchable monolayers.